Role Of Health Sector to Increase Public Awareness Through Educating the Community and Social Media Platforms: Case of Riyadh Saudi Arabia - Saad AlFlayyeh; Razan Ridha Fayzu (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Contemporary study aims to investigate the role of the health sector in educating the community and studying public awareness in Saudi Arabia. The country has a growing need for health education and awareness programs to address and prevalent health issues such as non-communicable diseases (NCDs), diabetes, hypertension, and obesity, among others. The paper will explore the current state of health education and awareness programs, their effectiveness, and potential for improvement. The research will also examine the perceptions of healthcare providers and the general public regarding the role of the health sector in promoting health education and awareness in the community. The study will use a convenience sampling technique to select a sample population of individuals residing in Saudi Arabia, who are 18 years of age or older, and have a basic understanding of health issues. The collected data analyzed using descriptive statistics, including frequency distribution, percentage analysis, mean, standard deviation, and correlation analysis. The findings of the study showed that there is a need to improve health education and awareness programs in Saudi Arabia to address these issues and promote healthier lifestyles among the population. The findings of this research can guide the development of effective and sustainable health education and awareness initiatives that address the prevalent health issues in Saudi Arabia.